2015
DOI: 10.1016/j.envint.2015.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of human hair as an indicator of exposure to organophosphate flame retardants. Case study on a Norwegian mother–child cohort

Abstract: A major challenge of non-invasive human biomonitoring using hair is to assess whether it can be used as an indicator of exposure to Flame Retardants, such as Organophosphate Flame Retardants (PFRs), since the contribution of atmospheric deposition (air and/or dust) cannot be neglected. Therefore, the aim of this study was to evaluate the suitability of using human hair more thoroughly by comparison of (i) levels of PFRs in human hair (from 48 mothers and 54 children), with levels measured in dust and air in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 41 publications
4
33
0
Order By: Relevance
“…A possible explanation for this could be that cats may be in direct contact with a possible source, as TBOEP is used in floor polishing products, as plasticizer in rubber and plastics (van der Veen and de Boer, 2012). The TBOEP concentration in the cat hair was comparable to levels previously reported in hair from children (Kucharska et al, 2015). TNBP and TEHP, which are mainly used as plasticizers but also as FRs (Dodson et al, 2012), had median concentrations of 294 and 175 ng/g in Vdust, 212 and 142 ng/g in F-dust and 22.5 and 20.9 ng/g in cat hair, respectively.…”
Section: Organophosphorus Flame Retardantssupporting
confidence: 82%
See 1 more Smart Citation
“…A possible explanation for this could be that cats may be in direct contact with a possible source, as TBOEP is used in floor polishing products, as plasticizer in rubber and plastics (van der Veen and de Boer, 2012). The TBOEP concentration in the cat hair was comparable to levels previously reported in hair from children (Kucharska et al, 2015). TNBP and TEHP, which are mainly used as plasticizers but also as FRs (Dodson et al, 2012), had median concentrations of 294 and 175 ng/g in Vdust, 212 and 142 ng/g in F-dust and 22.5 and 20.9 ng/g in cat hair, respectively.…”
Section: Organophosphorus Flame Retardantssupporting
confidence: 82%
“…When comparing the three main OPFR groups, Cl-OPFR, alkyl-OPFRs, and aryl-OPFRs, the Cl-OPFRs dominate the profile in dust samples and the alkyl-OPFRs in cat hair. Previous studies have shown that there is a stronger correlation for alkyl-OPFRs between human hair and air than for dust (Kucharska et al, 2015). The dominance of alkyl-OPFRs in the hair might support the finding that indoor dust partly contributes to the pattern observed in the hair.…”
Section: Organophosphorus Flame Retardantssupporting
confidence: 63%
“…During the development of the extraction method, the identification of OHCs from internal incorporation or absorption through the outer layer of the hair shafts was considered. After extraction (as discussed below), the hair was subjected to digestion using a weak acid as previously described for human hair [31]. The results (not discussed in this paper) were ambiguous and no OHCs could be identified.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The results (not discussed in this paper) were ambiguous and no OHCs could be identified. The procedure for the extraction and clean-up was subsequently modified from previously described methods for the analysis of brominated and organophosphate flame retardants in dust and human hair [31][32][33]. Two grams of unwashed/untreated hair was cut into small pieces ( < 5 mm) using pre-cleaned stainless steel scissors, added to clean amber glass vials, 30 mL of hexane/acetone (3:1, v/v) added, extracted by sonication in an ultrasonic bath (Brandson 8800, USA) for 10 min at 25 • C, followed by vortexing and centrifugation at 3500 rpm for 5 min.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Organophosphate ( Organophosphate triesters are susceptible to leaching from the products they are applied to due to abrasion and volatilization Marklund, 2005), and levels of OP triesters measured in house dust commonly exceed those of PBDEs (Meeker and Stapleton, 2010). Humans are primarily exposed through dermal absorption and inhalation of dust particles in indoor environments, and several biomonitoring studies have found detectable concentrations of OP triesters and (OP diester) metabolites in urine and hair samples (Butt et al, 2014;Cequier et al, 2014;Hoffman et al, 2015;Kucharska et al, 2015;Qiao et al, 2016;Su et al, 2016cSu et al, , 2015c. Consequently, leached OP triesters and degradation products are released into aquatic environments.…”
Section: Introductionmentioning
confidence: 99%